Sikap Guru terhadap Hasil Belajar Siswa Berkesulitan Belajar di Sekolah Dasar Negeri Penyelenggara Inklusif se-Kecamatan Pauh Padang - Tika Hendrawati (Universitas Negeri Padang, 2015)
Abstrak: The result is the achievement of one's learning in the learning process is performing. For students who have learning disabilities certainly more often get poor learning outcomes. There are several factors that affect the learning outcome itself. One of those factors is the teacher’s attitude. This research uses descriptive method with quantitative approach to see percentage of student opinion on the teacher’s attitude viewed from the aspect of cognitive, affective, and conative on student learning outcomes of student learning disabilities in primary inclusive schools at Pauh district using Padang . Technique of data collecting with questionnaire, resources of data come from student’s and teacher’s. The results were student’s opinion found have scrore there most (77.93%) teachers are seen from the cognitive aspect to be nice and receptive to learning disabilities students with learning results. Students found that almost all (80.50%) teachers' views of the affective aspect of being kind and receptive to learning disabilities students with learning results. Students found the majority score (77.92%) of teachers viewed from the aspect connative be nice and receptive to learning disabilities students with learning results. Kata kunci: Sikap Guru terhadap Hasil Belajar Siswa Berkesulitan Belajar.